Menilai Keanekaragaman Tumbuhan di Vegetasi Lantai Bawah Danau Laguna: Implikasi untuk Konservasi Keanekaragaman Hayati di Ternate - Natan, Sutriadin; Tabaika, Rosita; Umagap, Wirda AZ (Alpatih Harapan Semesta, 2024)
The forest floor vegetation is a layer of plants that grow near the soil surface and generally consists of shrubs, low bushes, herbs, and grasses. Erosion is the process of detaching soil particles from their original location, followed by the transportation of these materials by water or wind until they are deposited in another location. This study aims to analyze the diversity of floor vegetation types around Laguna Lake, Ngade Village, and to explain their role in reducing surface erosion. The research was conducted using a descriptive qualitative method with direct field observation. The research results show a variation in the types of ground vegetation in the three observation plots, where plot 1 contained 6 types, plot 2 consisted of 5 types, and plot 3 consisted of 5 types. Dominance analysis shows that there are no dominant types of vegetation in the three plots. This indicates that all types of vegetation work together to reduce surface erosion rates. The ground vegetation plays an important role in maintaining soil stability around Laguna Lake.